Successful Management of Neonatal Orbital Cellulitis: A Rare Case Report - Dian Estu Yulia; Kiara Nurmathias (The Indonesian Ophthalmologists Association (IOA, Perhimpunan Dokter Spesialis Mata Indonesia (Perdami)), 2022)
Objective: To report a rare case of neonatal orbital cellulitis along with the successful management. Introduction: Orbital cellulitis is a sight- and life-threatening infection of the post-septal tissues of the orbit, and is a considerably rare finding in neonates. Prompt diagnosis and treatment is essential, as 11-26% of cases of orbital cellulitis result in death and visual loss. Case Presentation: A one-month-old neonate presented with rapidly progressive swelling and redness of the right eyelid along with persistent subfebrile fever seven days before admission to the hospital. Blinking reaction to light stimulation was good on the left eye. Ocular motility was difficult to be evaluated. Conjunctival appearance on the right eye showed severe chemosis, while the other parts of both eyes were within normal limit. Orbital Computed Tomography (CT) scan revealed diffuse soft-tissue swelling at the superior and inferior palpebra of the right eye and partial erosion of the lateral wall of the right ethmoidal sinus, suggesting sino-orbital inflammation. Diagnosis of orbital cellulitis was confirmed on the right eye in this patient. Incision and drainage surgery of the right eyelids were done immediately as improvement was only seen on the upper eyelid after empirical intravenous (IV) antibiotic administration. Strain of Methicillin-Resistant Staphylococcus Aureus (MRSA) was found from the discharge’s culture. At one month follow up, the swelling of the right eyelid had markedly decreased with no signs of inflammation. Conclusion: This case highlights and showed a rare case and successful management of neonatal orbital cellulitis. Early diagnosis and prompt treatment of neonatal orbital cellulitis may benefit patient and prevent sight- and life-threatening condition.